2008
DOI: 10.1080/10408390701286058
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of Graded, Graphic and Text Label Presentations for Qualified Health Claims

Abstract: On December 18, 2002, the Food and Drug Administration (FDA) announced the Consumer Health Information for Better Nutrition Initiative. The initiative's goal is to make available more and better information about conventional foods and dietary supplements to help Americans improve their health and reduce risk of disease by making sound dietary decisions. It included a rating system to assess the "weight of the publicly available evidence." It assigns one of four ranked levels to the claim thus resulting in qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 7 publications
1
44
0
Order By: Relevance
“…Our result that the use of a qualifier has not much impact on claim perception is in line with other research (Kapsak et al 2008) and suggests that efforts at building a graduation of the strength of scientific evidence into the claim may be difficult to carry out. The finding that the direction of the small framing effect depends on the promised benefit is in line with results from van Kleef et al (2005) showing that effects of exact wording are minor and depend on the outcome promised.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result that the use of a qualifier has not much impact on claim perception is in line with other research (Kapsak et al 2008) and suggests that efforts at building a graduation of the strength of scientific evidence into the claim may be difficult to carry out. The finding that the direction of the small framing effect depends on the promised benefit is in line with results from van Kleef et al (2005) showing that effects of exact wording are minor and depend on the outcome promised.…”
Section: Discussionsupporting
confidence: 92%
“…Such qualification may be incorporated into the health claim by simply adding words like "may" or "can" (this product may reduce blocking of arteries) or by more elaborate devices like a rating of the strength of the scientific evidence (as suggested by the FDA). Again, findings have not been clear, with some studies indicating that consumers were confused by the qualifications (Kapsak et al 2008) or even attributed more certainty to claims with disclaimers compared to those without (Derby and Levy 2005).…”
Section: Introductionmentioning
confidence: 94%
“…However, Grunert et al (30) reported results showing that two types of consumers can be distinguished, those who prefer short messages and those who prefer more detailed information on health claims. Another way to increase consumer acceptance of claims may be to split the claim into a succinct statement on the front of the package and more detailed information provided elsewhere on the package (4,28) . Whether the claim is framed positively or negatively also may impact on consumers' reactions ('improves bone health' v. 'reduces risk of osteoporosis'), as does including a qualifier (e.g.…”
Section: Wording Of Claimsmentioning
confidence: 99%
“…Nevertheless, other studies have yielded contradictory results (22,26,27) . As general health claims tend to be shorter (28) , easier to understand and evoke positive associations from memory (29) , they may be more likely to be preferred by consumers (4,26) . This might explain why some studies reported disease risk reduction claims to be perceived as less credible and less attractive than general health claims, as was the case for Belgian (22) , Irish (27) and Nordic (30) consumers.…”
Section: Health Claim Formatmentioning
confidence: 99%
“…It gives the opportunity to get a product to market more quickly and thereby enhances the possibilities for food industries to grow and compete internationally (Hooker and Teratanavat, 2008;Lalor and Wall, 2011). However, the effect of graded health claims on consumers seems to be less positive: various studies show that consumers are not able to distinguish between the graded claims with qualifying language and health claims without qualifying language (Hasler, 2008;Hooker and Teratanavat, 2008;Kapsak et al, 2008;Lalor and Wall, 2011;Verhagen et al, 2010). It could therefore be interesting to focus on using emerging scientific evidence as substantiation for claims that influence a consumer's perception of health less directly, as is suggested for nutrition claims.…”
Section: Emerging Scientific Evidencementioning
confidence: 92%